Prospects for the development of complex injection molding of the cast alloy of the Al-Si system during the hardening process - Selivorstov , V.Yu.; Dotsenko , Yu.V.; Selivorstova , T.V. (Theory and Practice of Metallurgy, 2024)
The results of analytical studies of the effectiveness of the joint use of the processes of pressure influence and modification on the crystallization of alloys of the Al-Si system are presented. A complex technology of gas-dynamic influence and modification on the melt in the casting mold is presented, which allows to grind the structural components and increase the mechanical and operational properties of the cast products. The expediency and possibility of a complex effect of modification and gas pressure on the structure formation process of the AK5M cast alloy is theoretically substantiated. Casting "Conveyor rack support tip" made of AK5M alloy (DSTU 2839-94) weighing 1.1 kg was poured at a temperature of 710±10°C into a heated and painted cast iron mold with a minimum wall thickness of 40 mm. The content of the modifier (EUTEKTAL T200) in the melt was from 0.1 to 0.3 wt.%. The mechanical properties of the metal of the castings were determined according to the standard method. Analysis of the macrostructure of castings was performed using the BIAM sparring scale. The gas sparsity of casting templates was determined on three squares with a plane of 1 cm2 each. The number of pores and their size were determined as the arithmetic mean of three measurements. The degree of roughness of the macrocuts in points was established by comparing them with the standards of the scale. The analysis of literary sources on the topic of the work showed that the complex impact on the crystallizing metal, including the processes of modification and pressure application, is promising from the point of view of improving the mechanical properties of alloys of the Al-Si system. The given data show the prospects of development and use of complex technologies for processing alloys of the Al-Si system both at the stage of preparing the melt for pouring and at the stage of forming the casting directly in the foundry mold. As a result of the implementation of the mentioned technology, the number of defective castings on the bulkheads and gas sinks was reduced by 28%, the plastic properties of the cast metal increased by 25%, it was possible to reduce the amount of modifier by 15-20%, as well as reduce the temperature and processing time.